Effects of metacognitive ability and selective attention ability on academic performance of adolescents - Ahmad, Nuzhat; Sultana, Most Aeysha (Dhaka University Journal of Biological Sciences, 2021)
The present study investigated the effect of metacognitive ability and selective attention on academic achievement; whether selective attention and metacognitive ability influence a student’s academic achievement and whether all these three variables vary across gender. Three hundred adolescents were selected conveniently and purposively among which 150 were females and another 150 were males. Participant’s metacognitive ability was measured by using a Bangla translated version of Metacognitive Skill Scale (MCT); and selective attention was measured by a Bangla version of the Stroop Color and Word Test (SCWT). Their academic achievement was assessed by their GPA in previous class examination. The results showed that all these variables were significantly correlated with each other. Metacognitive ability and selective attention were the strong predictors of academic achievement. Significant difference in selective attention was also found across gender where females outperformed males. But no significant difference between males and females was found for the metacognitive ability and academic achievement. Dhaka Univ. J. Biol. Sci. 30(1): 59-67, 2021 (January)